215k views
12 votes
Can someone help im struggling real hard

Can someone help im struggling real hard-example-1

2 Answers

7 votes
(8x-9) + 3x = 90

8x + 3x -9 = 90

11x = 99

x = 99/11 = 9


3x = 3(9) = 27

8x-9 = 90 -27 = 63
User Manel
by
5.1k points
7 votes

Answer:

(8x - 9)˚ = 63˚

and

(3x)˚ = 27˚

Explanation:

heeyyyyy remember me?

Complementary angles are angles that equal 90˚, so we can create an equation:

(8x - 9) + 3x = 90

Remove the paranthesis

8x - 9 + 3x = 90

Add 9 to both sides

8x + 3x = 99

Simplify

11x = 99

divide both sides by 11

x = 9

So if we plug in x for 9 we get:

8x - 9

8(9) - 9

72 - 9

63

3x

3(9)

27

So

(8x - 9)˚ = 63˚

and

(3x)˚ = 27˚

User Edythe
by
4.6k points